2023
DOI: 10.3390/d15050649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Events on Abundance and Distribution of Major Commercial Fishes in the Beibu Gulf, South China Sea

Abstract: Improving prediction of ecological responses to climate variability requires understanding how local fish population dynamics are impacted by climate events. The present study was conducted in the Beibu Gulf of the northwestern South China Sea where the fisheries are characterized by high ecological and commercial value. We evaluated the relationship between major commercial fish population dynamics (abundance and distribution) and climate periods, using survey data from 2006–2020. The analysis using random fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Despite being a traditional fishing ground with high fishery yields in China, previous research has shown that the fishery ecosystem in the Beibu Gulf has significantly degraded due to overfishing [16]. The biomass and abundance of fishing targets, including D. maruadsi and T. japonicus, have decreased significantly [17]. Obviously, previous fishery management policies have not effectively prevented the decline of fishery resources in the region as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a traditional fishing ground with high fishery yields in China, previous research has shown that the fishery ecosystem in the Beibu Gulf has significantly degraded due to overfishing [16]. The biomass and abundance of fishing targets, including D. maruadsi and T. japonicus, have decreased significantly [17]. Obviously, previous fishery management policies have not effectively prevented the decline of fishery resources in the region as a whole.…”
Section: Introductionmentioning
confidence: 99%